Flexural capacity of continuous reinforced concrete beams strengthened or repaired by CFRP/GFRP sheets. (January 2021) - Ali, Harith; Assih, Jules; Li, Alex
Abstract: The flexural strengthening of reinforced concrete (RC) beams by bonding external composite materials has proved to be an effective and convenient technique. Several works, focus on mechanical behaviour of continuous reinforced concrete beam with two spans strengthened by composite materials, were reported in literature. This paper presents the flexural capacity of continuous RC beams with three spans strengthened or repaired by bonding carbon or glass fibre reinforced polymer (CFRP or GFRP) sheets. Experimental program consists of eight continuous RC beams strengthened by CFRP or GFRP sheets and one beam of reference. The dimension is the same for all beams with a length 9 m and a section 15x25 (cm). Experimental tests with monotonic loading were carried out by varying damaged level of the beams, composite material type and strengthening thickness. Five failure modes of strengthening beams were observed. The results show that the ultimate bending moment of the beam can be improved between 14.8 and 26.6% in case of the beams by bonding CFRP sheets and between 7.2 and 11.8% by bonding GFRP sheets. The beam, which was pre-damaged under pre-loading level 100% of the failure load, can be repaired as strengthened continuous RC beam. The optimal strengthening thickness in the positive and negative bending moment region was obtained. The variation of the strain in the positive and negative bending moment was analysed.